Utilization of Epididymal Sperm in Reproductive Technology - Muhammad Rizal; Nasrullah . (Indonesian Center for Animal Research and Development, 2004)
Cauda epididymal sperm could be used as an alternative of male gamete source for application in reproductive technology, because the sperm is motile and has ability for fertilizing oocyte. This sperm could be collected from life or death animal, then it might be processed for chilling or freezing. Epididymis from death animal could also be preserved at 5°C for several days before collecting and processing. Cauda epididymal sperm which has motility more than 40% can be applied for artificial insemination (AI) or in vitro fertilization (IVF) programs. Key words: Cauda epididymal spermatozoa, Al, IVF